Da-Huang-Xiao-Shi decoction protects against3, 5-diethoxycarbonyl-1, 4-dihydroxychollidine-induced chronic cholestasis by upregulating bile acid metabolic enzymes and efflux transporters. (6th April 2021) - Xue, Haoyu; Fang, Su; Zheng, Min; Wu, Jiasheng; Li, Hongyu; Zhang, Mengdie; Li, Yuanyuan; Wang, Tianming; Shi, Rong; Ma, Yueming
Abstract: Ethnopharmacological relevance: Chronic cholestasis is a usual clinical pathological process in hepatopathy and has few treatment options; it is classified under the category of jaundice in Chinese medicine. Da-Huang-Xiao-Shi decoction (DHXSD) is a classic Chinese prescription which is used to treat jaundice. Aim of the study : We aimed to examine the protective effect of DHXSD on liver and its potential mechanism of action against chronic cholestasis. Materials and methods: Chronic cholestasis was induced using 3, 5-diethoxycarbonyl-1, 4-dihydroxychollidine (DDC) in mice. Mice were then administered DHXSD intragastrically at doses of 3.68, 7.35, and 14.70 g/kg for four weeks followed by further analyses. Serum biochemical indices and liver pathology were explored. Eighteen individual bile acids (BAs) in mice serum and liver were quantified using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). The expression of BA related metabolic enzymes, transporters, along with nuclear receptor farnesoid X receptor ( FXR ) was detected by real-time qPCR and Western blot. Results: DHXSD treatment reduced the serum biochemical indices, ameliorated pathological injury, and improved the disordered BA homeostasis. Mice treated with DHXSD showed significantly upregulated expression of the metabolic enzymes, cytochrome P450 2b10 ( Cyp2b10 ), Cyp3a11, and UDP-glucuronosyltransferase 1a1 ( Ugt1a1 ); and the bile acid transporters, multidrug resistance protein 2 ( Mdr2 ), bile salt export pump ( Bsep ), and multidrug resistance-associated protein 3 ( Mrp3 ). DHXSD treatment also significantly upregulated FXR expression in mice with DDC-induced chronic cholestasis. Conclusions: DHXSD exerted protective effects on chronic cholestasis in DDC-treated mice by alleviating the disordered homeostasis of BAs through increased expression of BA related metabolic enzymes and efflux transporters. Graphical abstract: Image 1